2001
DOI: 10.1046/j.1365-2796.2001.00787.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep‐disordered breathing and glucose metabolism in hypertensive men: a population‐based study

Abstract: Abstract. Elmasry A, Lindberg E, Berne C, Janson C, Gislason T, Awad Tageldin M, Boman G (Uppsala University, Akademiska Sjukhuset, Uppsala, Sweden; Ain Shams University, Cairo, Egypt; and Vi®lsstadir Hospital, Gardabaer, Iceland). Sleepdisordered breathing and glucose metabolism in hypertensive men: a population-based study. J Intern Med 2001; 249: 153±161.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
118
0
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(135 citation statements)
references
References 36 publications
(39 reference statements)
9
118
0
6
Order By: Relevance
“…Several studies have shown an increased prevalence of sleep apnea and sleep disordered breathing in patients with diabetes mellitus type II (62,81). Mondini and Guilleminault (82) reported increased frequency of abnormal breathing during sleep in lean and obese diabetics.…”
Section: Sleep Apnea and Diabetesmentioning
confidence: 99%
“…Several studies have shown an increased prevalence of sleep apnea and sleep disordered breathing in patients with diabetes mellitus type II (62,81). Mondini and Guilleminault (82) reported increased frequency of abnormal breathing during sleep in lean and obese diabetics.…”
Section: Sleep Apnea and Diabetesmentioning
confidence: 99%
“…Obstructive sleep apnea syndrome (OSAS) is defined as repetitive decreases or cessations of airflow during sleep (1) and is associated with a wide array of cardiovascular (2) and metabolic risks (3,4), and is therefore linked to an elevated cardiovascular morbidity and mortality. Interestingly, part of the risk profile appears to be shared by patients suffering from adult GH deficiency (GHD) syndrome (5).…”
Section: Introductionmentioning
confidence: 99%
“…Obstructive sleep apnea (OSA) is very common in patients with type 2 diabetes (T2D) (6)(7)(8)(9)(10). We previously reported that OSA is associated with peripheral neuropathy, nephropathy, and estimated glomerular filtration rate decline in patients with T2D independently of obesity (10,11).…”
mentioning
confidence: 99%